STRATEGI HUMAS DINAS PERHUBUNGAN DARAT DKI JAKARTA DALAM MENGATASI KEMACETAN LALU-LINTAS DI IBUKOTA - Dewi, Yuni Retna (Universitas Prof. Dr. Moestopo (Beragama), 2014)
The focus of the problem is, âHow is the strategy of Land Transportation Office of Public Relations Jakarta to address traffic congestion in the capitalâ .Strategi is essentially planning (plan) and management to achieve one goal. According to Ruslan Rosady meaning of the strategy is: âan integrated part of a plan (plan), while the plan is the product of a planning (Planning), which in turn planning is one of the basic functions of the management processâ .Strategi Terrestrial Relations Public Relations Jakarta in address traffic congestion can be summarized as follows: Compliance with the implementation of the Act and Regulations traffic; coordination efforts (Synergy through coordination seek solutions and advice with discordant-related agencies such as the Department of traffic and Road Transport (DLLAJR); Office Traffic police; Hansip, Municipal Police; Department of Education; the military in times of emergency, and other agencies): Empowerment media (Synergy with the Jakarta Government and business media, Public Relations Jakarta Land Transportation pursuing a strategy in the form of an appeal to road users highway through the mass media: traditional, print, and electronics has been done. Even RASOGEL (Sonder radio waves) that is used by traffic police appeal to public road users so orderly and obedient with a loudspeaker); Empowerment Resources with the Government of DKI Jakarta Teknologi.Bersinergi put through the empowerment of technology resources include the installation of electronic signs, CCTV Control, electronic timer lamp, Model Busway, Doublereil Electric Railway, (the settlement plan Monoreil) and still in the plan of mass transit trains under land and river transportation empowerment. Efforts to use Model Nine Steps of Strategics PR, TCâS Of Public Relations Communication and Public Relations Planning Strategy aims to address challenges associated with congestion control strategy in Jakarta)